2021
DOI: 10.2478/ata-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Organic Waste Conversion Via Continuous Anaerobic Co-Digestion of Oil Palm Empty Fruit Bunches and Cow Manure: Evaluation of Feeding Regime on Methane Production

Abstract: Anaerobic co-digestion of oil palm empty fruit bunches with cow manure was studied. The research focus was on the evaluation of feeding different solid concentrations of the substrate in the on-going process of anaerobic digestion. The solid concentrations ranged from 0.5 to 12% TS. Results of the study showed that the maximum methane production could be reached with the reactor digesting substrates with 4 to 8% TS, in which the methane produced was from 1300 to 1400 mL per day. A significant drop of pH from 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This could be seen on the culture pH during the decomposition process in which the pH was stable at the level of 7.06. This indicated that the culture pH was still in the range of an ideal pH for running anaerobic digestion and/or anaerobic composting process [23,28]. The current study was in agreement with the study by Zorpas et al [29] revealing that the optimum pH values for the bacterial development on the processing of anaerobic compost production are from 6 to 7.5.…”
Section: Resultssupporting
confidence: 91%
“…This could be seen on the culture pH during the decomposition process in which the pH was stable at the level of 7.06. This indicated that the culture pH was still in the range of an ideal pH for running anaerobic digestion and/or anaerobic composting process [23,28]. The current study was in agreement with the study by Zorpas et al [29] revealing that the optimum pH values for the bacterial development on the processing of anaerobic compost production are from 6 to 7.5.…”
Section: Resultssupporting
confidence: 91%
“…The water content was measured by a laboratory heating and drying oven, in which the sample was heated for approx. 24 h at 105 °C (Rice et al 2017;Darwin et al 2019b;Darwin et al 2021b). The flash, fire cloud and pour points were measured using a laboratory hot plate equipped with a digital thermocouple.…”
Section: Resultsmentioning
confidence: 99%
“…During the processes of selective enrichment and fermentation, pH of the culture was regularly recorded utilizing a Lab Benchtop pH meter multifunction with complete probe. The pH meter was calibrated and validated with buffer solution prior to the measurements [32,33].…”
Section: Methodsmentioning
confidence: 99%